MRI of the Gastrointestinal Tract - Stoker, Jaap (Diagnostic Imaging,, 2010)
MRI has become an important tool in the management of patients with diseases of the gastrointestinal tract, such as rectal cancer and inflammatory bowel diseases. This book, written by distinguished experts in the field, discusses in detail the technical, practical, and clinical aspects of MRI of the gastrointestinal tract. The chapters on technique encompass the most recent developments and address such topics as contrast media, high field strength MRI, and perfusion MRI. Subsequently, individual chapters are devoted to the clinical applications of MRI in the different parts of the gastrointestinal tract. Both established applications and new frontiers are considered, with the aid of numerous high-quality illustrations. By combining chapters dedicated to technical aspects and clinically oriented chapters, this book will prove very instructive for the novice while simultaneously offering experienced practitioners further insights into the value of MRI of the gastrointestinal tract.